Gallstones in patients with inherited hemolytic diseases - Abdullah, Uday Y.H.; M. Jassim, Haitham; A. Baig, Atif; M. Khorsheed, Rana; Al-Khayat, Ali M. H.; Sulong, Ahmad Fadzli; Abed, Nagham F.; Yassin, Wisam A. (Academic Sciences, 2015)
The purpose is to provide an overview on the incidence of gallstone disease in patients with various types of inherited (chronic) hemolytic diseases at risk of cholelithiasis/choledocholithiasis with particular emphasis on its pathogenesis, genetic, risk factors and management. A detailed electronic literature search to determine the source of materials for this review article was done. The reported incidences of gallstones and choledocholithiasis vary according to the different types of inherited hemolytic diseases and the ethnicity of the studied populations. To date, no review article summarises the incidences of cholelithiasis in patients with various inherited haemolytic diseases was published. Regular ultrasound examination for the presence of gallstones recommended in patients with inherited haemolytic anaemias, particularly those with additional risk factors recommended. Further studies for evaluating the reasons for the higher incidence of cholelithiasis in thalassemia major and sickle cell anemia compared to hereditary spherocytosis; the effect of co inheritance of alpha thalassaemia on decreasing bilirubin level in patients with sickle cell disease and beta thalassaemia; the effect of the co inheritance of UGT1A1 and ABCG8 gene mutation on the incidence of gallstones in other blood diseases such as Hb-H disease, autoimmune haemolytic anaemias, congenital dyserythropoietic anaemia, hereditary elliptocytosis, Southeast Asian Ovalocytosis, glucose-6-phosphate and pyruvate kinase deficiency are recommended. Evaluation of the potential role of the solubility of the mutant proteins and haemoglobin subunit in the red blood cells as an additional mechanism for the development of gallstones in patients with inherited haemolytic anaemias recommended.